Use of phrasal verbs in an ESL learner corpus and its corresponding pedagogic corpus - Zarifi, Abdolvahed; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2019)
Phrasal verbs are one of the most notoriously puzzling aspects of English language instruction. Despite their potential complexities, they are of high relevance for ESL/ EFL learners because knowledge of them is often equated with language proficiency and fluency. With the emergence of corpus linguistics, phrasal verbs have been extensively studied in General, Learner and Pedagogic corpora. Literature, however, is lacking in how learners’ use of phrasal verbs reflects the corresponding pedagogic corpora to which they are exposed. To fill this research gap, this study adopted a corpus-based content analysis as its methodological approach to investigate the treatment of phrasal verbs in an ESL learner corpus and its corresponding pedagogic corpus. Findings are also compared against the presentation of these combinations in the British National Corpus (BNC). The study reveals that the selection of teaching materials is more intuitively than empirically based. It also suggests that teachers can use available corpora as supplementary teaching sources to work out the areas of L2 that tend to cause problems for the learners.